Phytochemical Profile and Pharmacological Potentials of Solanum dubium (Fresen.) - Wadah Osman; Mohamed Mirghani; Aisha Mohamed Kosar; Fatuma Ibrahim Mohamed; Khadijah Ghalgan; Mohammed H. Alqarni; Ahmed I. Foudah; Ahmed Ashour; Tariq M. Aljarba; Reham M. Samra (Natural Resources for Human Health, 2026)
Solanum dubium Fresen. is a species of the Solanaceae family. It is an indigenous wild plant of Sudan and other East African countries. The aim of this review is to explore and analyze its phytochemical constituents and pharmacological activities. The review followed the Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) 2020 checklist guidelines. The study involved searching in reputable electronic databases, such as PubMed, ScienceDirect, and Google Scholar. Only 21 articles were deemed eligible for inclusion in this review. Phytochemical groups are abundant in Solanaceae family and Solanum species, demonstrating various pharmacological properties. Few published studies (n = 6) have focused on isolation and identification of compounds, mainly from the seeds, while secondarily from aerial parts, whole plant, and leaves. Further investigations of the phytochemical composition of all organs are recommended due to the presence of alkaloids, sterols, and coumarins. In addition, few articles have focused (n = 17) on pharmacological properties, including antioxidant and antimicrobial activities. All pharmacological studies have focused on the seeds, fruits, whole plant, aerial parts, and leaves. The plant shows significant antioxidant activity, which helps in discovering the molecules used for treating many related oxidative stress diseases. Regarding cytotoxic activity, the plant has been only examined, in vitro, by using hepatic, lung and renal cell lines. Additional research is recommended for other pharmacological properties, focusing on all plant organs. Moreover, research is required for anticancer properties as well as other related oxidative stress diseases by using various cell lines in vivo and clinical validations.